2008
DOI: 10.1007/s15010-008-6306-1
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Guidelines on Empiric Use of Antibiotics in the Emergency Room

Abstract: Physicians' compliance with hospital guidelines to empiric antibiotics in ER was high. Adherence to guidelines was associated with a better outcome. Local susceptibility patterns to antibiotics need to be actively monitored. Prompt administration of antibiotics in the ER is likely to have a favorable outcome on survival, yet larger studies are required to establish this conclusively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…A Canadian study evaluating concordance with guidelines for antibiotic prescriptions for all infection‐related illness in community practices and reported that 39% of antibiotic prescriptions were not adherent to guidelines [15]. An Israeli study of physician compliance to hospital guidelines for empiric use of antibiotics in emergency rooms, reported a non‐adherence rate of 11.6% [16]. Comparisons of the above study findings were not feasible as rates of adherence to antibiotics prescription may be dependent upon patient disease and settings.…”
Section: Discussionmentioning
confidence: 99%
“…A Canadian study evaluating concordance with guidelines for antibiotic prescriptions for all infection‐related illness in community practices and reported that 39% of antibiotic prescriptions were not adherent to guidelines [15]. An Israeli study of physician compliance to hospital guidelines for empiric use of antibiotics in emergency rooms, reported a non‐adherence rate of 11.6% [16]. Comparisons of the above study findings were not feasible as rates of adherence to antibiotics prescription may be dependent upon patient disease and settings.…”
Section: Discussionmentioning
confidence: 99%
“…To include more resistant but often less prevalent pathogens, the empirical therapy of a severe infection is usually broad-spectrum. 5,10 The downside of this strategy is that the prescribed antibiotics are often more broad-spectrum than necessary 11 or even are used in the absence of a bacterial infection. 12,13 This may have potentially deleterious consequences such as anaphylactic reactions, antibiotic resistance, and high costs.…”
Section: Introductionmentioning
confidence: 99%
“…A high adherence of 90% to local antimicrobial therapy guidelines in patients with a suspected or documented infection (pneumonia, cellulitis or erysipelas, urosepsis, febrile neutropenia, or meningitis) has been described [8]. However, the investigated guidelines were developed by internal medicine specialists for their own use in patients admitted to the internal medicine wards or the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of the empirical antimicrobial therapy in sepsis mainly depends on the suspected site of infection and the antimicrobial susceptibility of the expected pathogens. To include more resistant but often less prevalent pathogens, the empirical therapy of a severe infection is usually broad-spectrum [4, 8]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation